Voltametri Pelucutan Anodik Menggunakan Elektroda Pasta Karbon Termodifikasi Bentonit untuk Penentuan Kadar Ion Cd(II) dalam Sayur Sawi Putih - Irdhawati, Irdhawati; Titasia, Ni Kadak Nevi; Sahara, Emmy (Universitas Andalas, 2021)
In this study, the measurement of Cd(II) ion by anodic stripping voltammetry technique was conducted using bentonite modified carbon paste as working electrode (CPE-B). The performance of CPE-B was compared with carbon paste electrode without bentonite (CPE) and applied for determination of Cd(II) concentration in chicory. Optimized parameters were composition of bentonite in carbon paste electrode, deposition time, deposition potential, and scan rate. Validation of measurements was observed including determination of linear concentration range, detection and quantization limits, repeatability of measurement, and percentage of recovery. The optimum composition of bentonite in CPE-B was found at 50%. Furthermore, in the optimization of measurements condition was found the optimum deposition times were 90 and 60 s, deposition potentials were -0.63 and -0.53 V, and scan rates were 15 and 20 mV/s, for CPE and CPE-B. The linear range concentration for CPE observed at 25-2000 µg/L and CPE-B was 5-50 µg/L. Limit of detection and quantization using CPE-B were 0.337 µg/L and 0.349 µg/L, lower than CPE i.e., 0.470 µg/L and 0.471 µg/L, respectively. Repeatability measurement of Cd(II) had Horwitz Ratio value less than two, and percentage of recovery was 96.73 8.33%. The level of Cd(II) ion in chicory was found at 6.98 0.40 mg/kg.